In the air Disc 3 - Wall to Wall Television; Learning Channel (Firm); Ambrose Video Publishing (New York, NY : Ambrose Video, 2001)
Three episodes from a 15-part series that looks at what is known about early man and animals from the fossil record, as well as how this information is known. Includes recent discoveries.
Flight of the Pterosaurs -- Dinos in the air -- Early birds.
Optional English subtitles.
Program content c1996.
DVD.
Keywords: Pterosauria; Extinct birds; Birds -- Evolution; Birds, Fossil; Archaeopteryx; Dinosaurs; Paleontology